The Mysteries of Money - Esposito, Elena (MAD, 2013)
This article addresses problems of the understanding of money in modern society. At present there is no adequate sociological theory to understand functions and specificities of money. Faced with this, the present article aims to define money in the context of a temporal dimension, specifically as a "medium of deferment". Some consequences of the monetarization of the economy of society and some characteristics of the economy of the "derivatives" are addressed. The article concludes with considerations concerning the new character of the monetary economy.